Employment status and HIV viral load in Chilean adult population: a propensity score analysis - Leiva-Escobar, Ignacio; Cortes, Claudia P.; Lamadrid, Angelo (Aids and behavior, 2025)
We set out to investigate the potential impact of unemployment on HIV viral load in individuals living with HIV at the biggest HIV-related healthcare centre in Chile. We analysed a cross-sectional dataset of 803 adults living with HIV on antiretroviral therapy. The main exposure was employment status. The outcome, detectable HIV viral load, was operationalised using a cut-off of HIV viral load at 20 copies/mL. We applied a propensity score method, the inverse probability of treatment weighting to control for measured confounders. We found that 219 (27.3%) of participants were unemployed. Being unemployed was associated with increased odds of being detectable (OR = 1.78, 95%CI = 1.18-2.71) compared to being employed. Additionally, we found that those unemployed and non-adherents have higher odds of being detectable (OR = 2.53, 95%CI = 1.18-5.41). Unemployment status may influence HIV viral load. However, further research is needed to determine and understand the social structure behind those relationships in the Chilean people living with HIV.
Gesehen am 09.10.2025